Ontogeny and transcriptional regulation of Thetis cells - Yoselin A. Paucar Iza; Tyler Park; Eliyambuya Baker; Gayathri Shibu; Tilman Hoelting; Greyson Feather; Anushka Yadav; Yollanda Franco Parisotto; Zihan Zhao; Blossom Akagbosu; Marc Elosua Bayes; Logan Fisher; et al. (Nature, 2026)
Abstract Thetis cells (TCs) are a recently identified lineage of RORγt + antigen-presenting cells comprising four subsets, TC I to TC IV, including a tolerogenic subset (TC IV) that instructs tolerance to gut microbiota and food antigens 1–6 . A developmental wave of TCs during early life creates a crucial window of opportunity for establishing intestinal tolerance 1,5 . The ontogeny of TCs and the cues that shape their abundance and heterogeneity remain unknown, however, limiting efforts to harness their therapeutic potential. Here we identify a population of RORγt + progenitors, termed Thetis–lymphoid tissue inducer progenitors (TLPs), that give rise to the immediate TC progenitor (TCP) and the lymphoid tissue inducer (LTi) progenitor (LTiP), and identify PU.1 as the transcription factor that governs TC fate. Despite transcriptional similarity to myeloid-derived conventional dendritic cells, we show that TCs descend from the common lymphoid progenitor. Deletion of the plasmacytoid dendritic cell (pDC) lineage-determining transcription factor TCF4 expands TLPs and TCs, indicating a shared developmental branch with pDCs. TLPs are enriched in fetal liver, but, unlike LTi cells, TCs emerge postnatally, indicating that developmentally timed environmental cues promote TCP differentiation. We identify one such cue, RANKL provision by lymphoid tissue organizer cells, that is essential for TC I differentiation. Together, these findings define the ontogeny of TCs and the transcription factors that promote TC differentiation and heterogeneity, facilitating future investigations of these enigmatic cells and their therapeutic potential for tolerance induction in food allergy and autoimmunity.